PRESIDENT JOKO WIDODO’S INTERPERSONAL STRATEGIES IN HIS SPEECH IN THE 2014 APEC CEO SUMMIT (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2016)
This study aims at describing the way President Widodo used his interpersonal strategies in his speech in the 2014 APEC CEO SUMMIT. In this study, the discussion was limited by finding out the interpersonal meaning of the speech which can be used to dig up speaker’s hidden meanings through what he is saying in the speech. This is a descriptive qualitative study. The concept of discourse analysis from the perspective of Systemic Functional Linguistic (SFL) is employed as a tool to reveal the hidden motivations behind a text. The analysis reveals that in terms of context of situation, President Widodo delivered persuasive speech. Meanwhile, grammar analysis shows that President Widodo was delivering speech in the name of Indonesia and in the name of Indonesian people who need a lot of economic capital in order to achieve the economic goals of Indonesia. In delivering his speech, President Widodo also strongly believed that he would be able to reach his goals. The appraisal analysis shows that Appreciation is the most frequent appraisal devices used in the speech. In that sense, President Widodo’s stance or attitude towards the goals he wants to achieve is strongly positive. It can be concluded that by the elaborate use of interpersonal strategies, President Widodo successfully projects his ideas and messages to the audience and also build a persuasive speech.